Meningkatkan Kualitas Pembelajaran Pada Mata Kuliah Pengantar Probabilitas Melalui Lesson Study Dengan Pengajaran Berbalik Secara Team - Agoestanto, Arief (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2012)
The quality of introduction to probability lectures that were held haven’t maximized yet. It is indicated by results of student learning that only 20% got A value, the lack of interaction between students and lectures, students with students, and students with lecture. One of the efforts to improve the quality of learning is through lesson study with team reciprocal teaching. The problem in this research are as follows: (1) is the lecturers’ professionalism of Statistics Expertise Group can be improved by Lesson Study approach in the introduction to probability lectures, and (2) is interaction between students and students, students with lecture note, and students with lecturers of introduction to probability lesson can be improved by apply lesson study method with team reciprocal teaching. This research use research model based on lesson study by three steps. They are plan, do, and see which are done in three cycles. The research was conducted on odd semester in academic year 2010/2011 for 6 months in Mathematics department, Semarang State University. The results of research are (1) the increasing of lecturers’ professionalism of Statistics Expertise Group for Introduction to Probability lectures, and (2) increase student interaction with students, students with lecture note, and students with lecturers of Introduction to Probability lectures.